Analisis Dampak Perubahan Tata Guna Lahan DAS Siak Bagian Hulu Terhadap Debit Banjir - Junius Nainggolan; Yohanna Lilis H; Sigit Sutikno (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
Historical data discharge in Upper Siak watershed is incrase event caused by the land use change. This study aims to analyze the effect of land use change on the flood discharge in Upper Siak watershed. This Study analyze flood discharge by using HEC-HMS (Hydrologic Engineering Centre-Hydrologic Modelling System) software with input data models in the form of daily rainfall data, land use maps of 2003 and 2012 and soil type maps. The result showed that there is significant changes in land use on land farming with icrease of 28,8 %, meanwhile there is changes in land use on forest with reduction to 34,4 %. Peak flood on 25-year return period incrase to 13,3 m3/s (5.9 %) and peak flood on the 50-year return period incrase of 14,1 m3/s (6.1 %).Keywords: land use change, flood discharge, HEC-HMS